Analysis of relay protection systems of regional distribution networks with distributed generation sources - Kaplun, V.; Remez, S. (Energy and Automation, 2025)
The article presents a comparative review and analysis of modern methods of functioning of relay protection systems of medium-voltage distribution networks with distributed generation sources (DGR). The analysis touched upon the main technical challenges associated with the active introduction of DGR, primarily renewable sources, into regional networks, which leads to a change in the directions of flows and currents in the network, violation of the conditions for ensuring selectivity, sensitivity and technically perfect coordination between protective devices. Special attention is paid to the features of relay protection of micro-power systems during the transition from network to island mode. The purpose of the study is to review and analyze modern methods and systems of relay protection of distribution regional networks with DRG, taking into account the features of their operation. The article studies traditional and innovative (adaptive, combined, based on sequential components, using phasor measuring devices and artificial intelligence) protection methods, their efficiency and ability to operate in characteristic modes. The comparative analysis was carried out taking into account known modern platforms, their advantages, complexity of implementation, requirements for communication channels, settings and tests, possible risks due to the complexity of relay protection systems. The key advantages and limitations of modern approaches to implementing relay protection, as well as current trends in the development of protection systems for active networks with a high share of DRG, are identified. It is shown that to ensure the reliability and safety of power supply in modern conditions, it is necessary to implement adaptive, intelligent and hybrid protection systems with the possibility of operating regional microgrids in island mode. As a rule, in distribution regional networks, protection systems based on current measurement are used, less often - based on voltage measurement or combined protection systems (based on current and voltage measurement). However, the change in the structure of power supply from centralized (with one-way current flow) to decentralized (with different DRGs) creates a serious threat to network protection systems in terms of reliability of operation, sensitivity and coordination of various protection elements. It is established that innovative methods demonstrate higher flexibility, accuracy and ability to self-organize. At the same time, they require more complex technical and software implementation, communication setup and relevant implementation experience. The reliability of protection in the future will be determined by the system’s ability to adapt to rapid changes in operating mode, dynamic connection and change of DRG parameters, requirements for power supply of critical consumers even in the event of a transition to islanding modes when disconnected from the main grid. Key words: distributed generation, transient stability, protection coordination, islanding, distribution networ.